Laboratory of genetics and physiology 2 (LGP2) plays an essential role in hepatitis C virus infection‐induced interferon responses. Issue 5 (30th March 2017) - Hei, Lei; Zhong, Jin
Abstract : Retinoic acid‐inducible gene I (RIG‐I)‐like receptors are cytosolic pattern recognition receptors (PRRs) that detect non‐self‐RNA and activate downstream interferon (IFN) signaling. One of the RIG‐I‐like receptors, laboratory of genetics and physiology 2 (LGP2), was originally thought to be a negative feedback regulator in the RIG‐I signaling pathway, but growing evidence indicates that LGP2 is one cofactor of melanoma differentiation‐associated protein 5 (MDA5) in MDA5‐mediated IFN signaling activation. Our previous work showed that MDA5 was the major PRR to sense hepatitis C virus (HCV) infection in hepatocytes, but the role of LGP2 in HCV infection‐induced IFN signaling has not been elucidated. In this study, we reported that LGP2 was a positive regulator of HCV infection‐induced IFN signaling. Knockout of LGP2 in hepatocytes significantly diminished IFN production in response to HCV infection, but not to HCV 3'untranslated region RNA transfection. Mechanistic studies showed that LGP2 exerted its function at a step upstream of MDA5 in the IFN signaling. HCV infection promoted the molecular interaction between LGP2 and MDA5, which, in turn, enhanced MDA5/HCV RNA association. Finally, we demonstrated that the ATPase activity of LGP2 was critical for assisting MDA5/HCV RNA interaction and activating IFN signaling during HCV infection. Conclusion : Our work demonstrated that LGP2 plays an essential role in activating IFN signaling against HCV infection by promoting MDA5 recognition of HCV pathogen‐associated molecular patterns. (Hepatology 2017;65:1478‐1491)